Spatial and temporal presence of diurnal raptors (aves: accipitriformes, falconiformes) at marismas nacionales, Nayarit-Sinaloa, Mexico - Carmona, Roberto Carlos; Mendoza, Luis F.; Molina, David; Ortega, Lidiana; Miramontes, Emmanuel; Cruz, Miguel (Instituto de Ecología, A.C., 2017)
Diurnal raptors are an essential group for balance in communities that can be used as habitat quality indicator owing to their sensitivity to disturbance. In Mexico one of the biologically significant areas and that faces serious anthropogenic issues is Marismas Nacionales. Comprehensive management and conservation assessments for the area will require to generate a baseline on poor studied group in Mexico such as raptors. Thus we determined spatial and temporal richness of diurnal raptors through eight months (November 2010 to June 2011) in nine sites of Marismas Nacionales, where we recorded and counted all species per site and month. In that period 945 records of 22 species were made, additionally other five species were observed on a subsequent visit (January 2012) therefore we had 27 species in total. Winter richness increased with the presence of four migratory species and decreased in summer. The most abundant species were the scavengers (Turkey vulture, Black vulture) and one migratory (Osprey); these three species comprised 65% of total records. We found the highest numbers of species in Zoquipan and Garzas-Chahuín (13 and 11 species respectively). In concern of total records, Zoquipan and Chumbeño presented the highest with 207 for the first and 185 the second one. The results shows a high richness of raptors in Marismas Nacionales due to its geographical position on the limit of two biogeographic regions (transition zone) and secondly by the variety of environments in the whole area. The scarce previous data makes difficult to compare any changes in species composition, which also avoid magnify the effect of habitat loss on this group.